Fiber to the Antenna : a closer look at benefits and issues in integrated optical and wireless networks - Haque, Fahimul; Chowdhury, Sheri Jahan; Ahsan, Sheikh Shazeed; Rahman, Md. Zamiur (BRAC University, 2014)
This thesis report submitted in partial fulfillment of the requirement for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2014.